2021
DOI: 10.3389/fonc.2021.712788
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution of Immune Cells in Head and Neck Squamous Cell Carcinomas

Abstract: BackgroundHead and neck squamous cell carcinomas (HNSCCs) have a very moderate response rate to immune checkpoint inhibitor (ICI) treatment compared to other cancer types. Lacking predictive markers for treatment response, we analyzed the immune status of HNSCC and assessed the spatial distribution of immune cells.Materials and MethodsVia assessing hematoxylin–eosin (H&E) stains, we divided HNSCCs by the immune cell distribution in hot, cold, and excluded tumors. For each group, each with 10 tumors, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
3
3
0
Order By: Relevance
“…CD8+, DCs, Natural killer immune cells) that facilitate clearance of tumor cells (46). A clinical trial indicated hot tumors have significantly higher expressions of PD-1 and PD-L1 in comparison to cold tumors, they might be more prone to immune checkpoint inhibitors treatments (47). Our results also confirmed that Cluster-C corresponds to abundant CD8+T cell infiltration and highly expressions of PD-1/PD-L1 compared to Cluster-A and Cluster-B.…”
Section: Discussionsupporting
confidence: 80%
“…CD8+, DCs, Natural killer immune cells) that facilitate clearance of tumor cells (46). A clinical trial indicated hot tumors have significantly higher expressions of PD-1 and PD-L1 in comparison to cold tumors, they might be more prone to immune checkpoint inhibitors treatments (47). Our results also confirmed that Cluster-C corresponds to abundant CD8+T cell infiltration and highly expressions of PD-1/PD-L1 compared to Cluster-A and Cluster-B.…”
Section: Discussionsupporting
confidence: 80%
“…Kouckýet al demonstrated a colocalization of functionally impaired pDCs with T regs in TS and reported a selective pDC-fostered T reg expansion (44). When looking at T cell subpopulations in our HNSCC cohort, T regs represented the major T H cell subset, with their predominant stromal distribution confirming current literature (45) and may contributing to the mentioned relation of pDCs and T regs . With respect to further T H subsets, T H 1 cells were more common than T H 2 cells or T H 17 cells and significantly more frequent in IET than in TS.…”
Section: Discussionsupporting
confidence: 86%
“…However, we found significantly higher CDK7 expression in immune-infiltrated tumor tissue. Previously we described higher TPS in immune-infiltrated tumors [48]. We suppose that CDK7 might drive higher PD-L1 expression in these tumors.…”
Section: Discussionmentioning
confidence: 59%